Fatigue Reliability Assessment for Orthotropic Steel Bridge Decks Considering Load Sequence Effects - Xu, Jun-Hong; Zhou, Guang-Dong; Zhu, Tai-Yong (Frontiers in Materials, 2021)
Fatigue damage accumulations would dramatically reduce the reliability and service life of the orthotropic steel decks. Incorrect fatigue assessment results may be obtained when load sequence effects are omitted. In the present study, fatigue reliability assessments of rib-to-deck weld joints in orthotropic steel bridge decks are conducted with the consideration of load sequence effects. The method, which judiciously considers the fatigue loading history and is derived from the sequential law and the whole-range S-N curve, is first proposed for fatigue reliability calculation. And then, the whole-range S-N curve describing the fatigue propagating process of the rib-to-deck weld joint is introduced. Finally, the developed method is applied to evaluate the fatigue reliability of two rib-to-deck weld joints in an orthotropic steel deck based on long-term measured strain histories. The influence of traffic growth and initial damage on the fatigue reliability is discussed. The results indicate that it is advisable to consider load sequence effects when assessing the fatigue reliability of orthotropic steel decks equipped with long-term strain monitoring systems and the initial damage significantly reduces the fatigue reliability of orthotropic steel decks.